Association between milk production and reproductive efficiency traits in Mpwapwa cattle and their crosses - Das, S.M.; Mgheni, M.; Msechu, J.K.K.; Mpiri, D.B. (1989)
Analysis of fifteen years (1970- 1984) data on Mpwapwa cattle (12% B. taurus) and their crosses, Backcross (34% B. taurus) and Crossline (56% B. taurus) was carried out. Data pooled over the first five lactations showed that for Mpwapwa, backcross and crossline cows, lactation milk yield averaged 1446.6, 1530.1 and 2209.3 kg; lactation length averaged 263.6, 270.4 and 288.2; calving interval averaged 446.5, 399.4 and 413.1 days; dry period averaged 172.5, 127.4 and 117.1 days; and days open averaged 167.3, 118.4 and 132.9 days, respectively. Estimates of repeatability for calving interval, dry period and days open were 0.07 ± 0.05, 0.21±0.05 and 0.12±0.04, respectively. Calving interval significantly influenced concurrent and subsequent lactation milk yield (b = 0.42 and b = 0.46, respectively). Correlation coefficients between days open and concurrent lactation milk (r=0.03) and lactation length (r=-0.07) were non-significant. Results from the analyses are discussed in relation to the reported levels of association of reproductive efficiency traits with milk production traits in previous studies elsewhere. It was concluded that cattle breeding programmes for milk production should pay attention to reproductive efficiency traits.